Pecundang dari Perdagangan Internasional: Studi Kasus Impor 28 Jenis Buah Musiman di Indonesia - Permana, I Gusti Agus Yudha; Sukadana, I Wayan (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 2, Agustus 2016 (pp. 89 - 176), 2017)
The quality of the Indonesian fruit production is actually insufficient to meet domestic consumption, the geographical condition, with its tropical climate is perfect for growing the seasonal fruit. This study aims to determine whether the imports of the 28 seasonal fruit, which is also grown domestically, put pressure on the domestic production. International trade theory states, imports will put pressure on the domestic producers. The data used to test these theories is the time series data from 1970 to 2012 of 28 types of seasonal fruit.We use the natural log for the import and also the domestic production instead of the nominal amount.The impactof Indonesian trade policy periodization also try to explain by using dummy variables in the standart regression model. The results showed the negative impact of imports on production of 28 types of the local fruit. Other results also show that in the period before the 1980 production was 53 percent higher than in the period after it, which the period wherethe economic openness are higher.
Keywords: impor; kebijakan perdagangan bebas; buah; produksi